Computer program to predict path loss in a mobile radio channel environment - Cheng, Weng Lock. (2008)
The objective of this thesis is to develop computer programs to predict path loss in mobile radio channel environment. Matlab® computing language is chosen because it is easier to program mathematical models into computing language. In this thesis, chapters 1, 2 and 3 are devoted to explanation of basic radio channel concepts, its complexities of prediction and the impact of the advantages of path loss prediction.